Genome-wide identification and characterization of FORMIN gene family in cotton (Gossypium hirsutum L.) and their expression profiles in response to multiple abiotic stress treatments - Suronjeet Kumar Paul; Md Shohel Ul Islam; Nasrin Akter; Fatema Tuz Zohra; Shuraya Beente Rashid; Md. Shakil Ahmed; Shaikh Mizanur Rahman; Md. Abdur Rauf Sarkar (PLoS ONE, 2025)
FORMIN proteins distinguished by FH2 domain, are conserved throughout evolution and widely distributed in eukaryotic organisms. These proteins interact with various signaling molecules and cytoskeletal proteins, playing crucial roles in both biotic and abiotic stress responses. However, the functions of FORMINs in cotton (Gossypium hirsutum L.) remain uncovered. In this study, 46 FORMIN genes in G. hirsutum (referred to as GhFH) were systematically identified. The gene structures, conserved domains, and motifs of these GhFH genes were thoroughly explored. Phylogenetic and structural analysis classified these 46 GhFH genes into five distinct groups. In silico subcellular localization, prediction suggested that GhFH genes are distributed across various cellular compartments, including the nucleus, extracellular space, cytoplasm, mitochondria, cytoskeleton, plasma membrane, endoplasmic reticulum, and chloroplasts. Evolutionary and functional diversification analyses, based on on-synonymous (Ka) and synonymous (Ks) ratios and gene duplication events, indicated that GhFH genes have evolved under purifying selection. The analysis of cis-acting elements suggested that GhFH genes may be involved in plant growth, hormone regulation, light response, and stress response. Results from transcriptional factors TFs and gene ontology analysis indicate that FORMIN proteins regulate cell wall structure and cytoskeleton dynamics by reacting to hormone signals associated with environmental stress. Additionally, 45 putative ghr-miRNAs were identified from 32 families targeting 33 GhFH genes. Expression analysis revealed that GhFH1, GhFH10, GhFH20, GhFH24, and GhFH30 exhibited the highest levels of expression under red, blue, and white light conditions. Further, GhFH9, GhFH20, and GhFH30 displayed higher expression levels under heat stress, while GhFH20 and GhFH30 showed increased expression under salt stress compared to controls. The result suggests that GhFH20 and GhFH30 genes could play significant roles in the development of G. hirsutum under heat and salt stresses. Overall these findings enhance our understanding of the biological functions of the cotton FORMIN family, offering prospects for developing stress-resistant cotton varieties through manipulation of GhFH gene expression.